Analisis Waktu Kebisingan PT. Riau Power Unit PLTG/U Pekanbaru Dengan Metode Noise Mapping - Rizka Agnestianova; Aryo Sasmita; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The Research has been conducted to determine the the noise’s intensityfrom operational activities originating from generating machines at PT. RiauPower Unit PLTG / U Teluk Lembu Pekanbaru with the Grid method. Workerswho are constantly exposed to noise have the potential to affect workers' healthand comfort. The purpose of this study was to determine the intensity of noisegenerated by the generator engine, the length of exposure time, mapping the noisedistribution patterns, and noise control efforts. The noise measurement methodrefers to the noise mapping method and the instrument used is a Sound LevelMeter (SLM). The measurement of sound pressure level took place for 1 day. Theresults showed that from 97 measurement spots there were 40 spots indicatingnumbers that exceeded the quality standard. The highest loudness level is 106.1dB where this spot located very close from the noise source, and the lowestloudness level is on 59.5 dB where the distance is quite far from the noise source.The planned noise control attempt is by using noise barrier (naturally orartificially), isolate the machines, machine care, the administration management,and the human resource management by applying a vertical garden to the officebuilding.Keywords : Noise , Noise Mapping, PLTG/U